Numerical Studies on CFRP Strengthened Cold formed Steel built-up Columns - chakravarthy H G, Nahushananda; S J, Jahnavi; Naganathan, Sivakumar (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper reports the numerical investigation carried out on the Cold-formed steel (CFS) built up columns strengthened with a Carbon fiber-reinforced polymer (CFRP) by using Finite element software ABAQUS/CAE. The CFS sections used in the investigation are built-up Cold formed box sections connected together by screws. Totally 24 columns are considered for the analysis in that twelve columns used are plain CFS and other 12 columns used are CFRP strengthened CFS columns. The geometric properties of the materials considered as 0.6 mm, 0.75 mm and 1 mm thickness with 300 mm, 500 mm and 700 mm depth respectively. All the built-up columns were modeled and analysed using ABAQUS software. From the analysis results, the Ultimate load capacity, Buckling behavior and Load-lateral displacement of the Plain and CFRP strengthened columns are obtained and presented in this paper. It is also noted that the numerical results obtained from the ABAQUS software is in good agreement with the experimental results.